Atomic-resolution investigation of structural transformation caused by oxygen vacancy in La0.9Sr0.1TiO3+δ titanate layer perovskite ceramics. (30th March 2022) - Zhao, Yang; Zhu, Yameng; Zhu, Jinpeng; Wang, Hailong; Ma, Zhuang; Gao, Lihong; Liu, Yanbo; Yang, Kaijun; Shu, Yongchun; He, Jilin
Highlights: The formation process, migration behavior, and microstructure effects of oxygen vacancies on overlapping layered structure perovskite La0.9 Sr0.1 TiO3+δ were investigated systematically. New discoveries enhance the understanding of lattice defects in layered perovskite oxides and the lattice transformation mechanism caused by oxygen vacancies on atomic-resolution scale. Providing an approach to reveal how oxygen vacancy disables lower optical property in layer perovskite functional materials. Abstract: Perovskite functional ceramics have been widely applied for thermal protection owing to their unique physical properties. However, formation of oxygen vacancies under external stimuli usually limits their performance in practical applications. Therefore, the mechanism of the effect of oxygen vacancy on the layer structure of perovskite La0.9 Sr0.1 TiO3+ δ was investigated by experiments and first-principles simulations. The experimental results showed that the lattice distortion occurred in oxygen-deficient environment to give a longer c -axis, along with a significant adjustment in the modes of A/B–O bond vibration, resulting in lower reflectivity. Advanced transmission electron microscopy studies revealed that oxygen vacancies induced localized atomic rearrangements via [TiO6 ] layer movements to adapt to the lattice distortion. This eventually restructured a part of the layer interfaces by expanding the overlapping projection of atoms in the c -axial direction. The specific transformation process was described as a compendious process, while geometric phase analysis effectively clarified how oxygen vacancies can inhibit reflectivity on the layer structure. Thus, this study provides effective approaches for researching the effects of oxygen vacancy on the physical properties of orthorhombic layer perovskite structures, which may facilitate the development of perovskite-based functional devices. Graphical abstract: Image, graphical abstract